Magnetic lipid nanocapsules (MLNCs): self-assembled lipid-based nanoconstruct for non-invasive theranostic applications. Issue 7 (17th January 2018) - Nandwana, Vikas; Singh, Abhalaxmi; You, Marisa M.; Zhang, Gefei; Higham, John; Zheng, Tiffany S.; Li, Yue; Prasad, Pottumarthi V.; Dravid, Vinayak P.
Abstract : A novel magnetic nanostructures (MNS) stabilized lipid nanoconstruct is reported that shows superior structural stability and theranostic functionality than conventional lipid based nanocarriers. Abstract : We report magnetic nanostructure-stabilized lipid nanocapsules (MLNCs) that show superior structural stability and theranostic properties compared to conventional lipid-based nanocarriers. As therapeutic nanocarriers, the MLNCs exhibit a therapeutic efficacy that is 16 times greater than that of free drugs due to their high payload capacity and actuated drug release ability. In addition, the magnetic resonance contrast enhancement of the MLNCs is nine times higher than that of a clinically approved T 2 MRI contrast agent (ferumoxytol), demonstrating the diagnostic imaging capability of the MLNCs in MRI. The self-assembly method to synthesize the lipid nanocapsules is extended to other types of nanoparticles (gold nanoparticles and quantum dots) to produce lipid nanohybrids with distinct physical properties.